2014
DOI: 10.1007/s11845-014-1098-z
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular effects of long-term caffeine administration in aged rats

Abstract: Long-term caffeine administration in aged rats increased cardiac inotropy, lusitropy and preserved NO level, which points to a promising potential favorable effect on cardiac intrinsic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…In the present study, the MDA concentration after administration of caffeine to diabetic rats was lower both in the lens and serum, as compared with the control diabetic animals. This observation is consistent with that made in old rats (18–20 months), in which caffeine administered at 25 mg/kg for 6 weeks reduced the MDA concentration in the serum [11].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, the MDA concentration after administration of caffeine to diabetic rats was lower both in the lens and serum, as compared with the control diabetic animals. This observation is consistent with that made in old rats (18–20 months), in which caffeine administered at 25 mg/kg for 6 weeks reduced the MDA concentration in the serum [11].…”
Section: Discussionsupporting
confidence: 92%
“…Caffeine has been reported as a protective substance against cellular damage with beneficial antioxidant effects [810]. Intake of caffeine is associated with reduced levels of biomarkers of oxidative stress [1115]. Caffeine is able to scavenge ROS, particularly the hydroxyl radical, known to be generated in the body by exposure to ultraviolet light and by many physiologic reactions involving oxygen utilization [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…The acute effects of caffeinated beverages on electrocardiographic parameters were evaluated in various studies 7,8,19 . Most of them reported that PR interval and QRS complex were not changed after caffeinated beverage consumption 19,23,41 . This was consistent with our results.…”
Section: Discussionmentioning
confidence: 99%